2005
DOI: 10.4161/cc.4.9.1975
|View full text |Cite
|
Sign up to set email alerts
|

Human CDK2 Inhibition Modifies the Dynamics of Chromatin-Bound Minichromosome Maintenance Complex and Replication Protein A

Abstract: Previously published as a Cell Cycle E-publication: http://www.landesbioscience.com/journals/cc/abstract.php?id=1975 KEY WORDSCDK2, MCM4, RPA, ATR, re-replication, MCM2, checkpoint ACKNOWLEDGEMENTSWe thank all members of the Lead Identification Laboratory for initial studies of CDK2 inhibitor; members of Oncology group in the Department of Discovery Research for helpful discussions; and Scott Frank, Larry L'Italien, Loren Russell, Xiao Min Schebye for CDK2, CDK1, and cyclin E siRNAs validation and retroviral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
(66 reference statements)
3
16
0
Order By: Relevance
“…Even though geminin is not degraded after DNA damage (Higa et al, 2003 and our unpublished observations), the persistence of geminin during a checkpoint response is not sufficient to block substantial preRC reassembly. This assertion is supported by previous findings that direct inhibition of Cdk activity during G2, either pharmacologically or genetically, permits reloading of MCM proteins onto chromatin even in the presence of geminin (Bates et al, 1998;Ballabeni et al, 2004;Zhu et al, 2005). Thus, there is a risk of genome instability if preRCs are permitted to assemble while Cdk activity is inhibited.…”
Section: Discussionsupporting
confidence: 69%
“…Even though geminin is not degraded after DNA damage (Higa et al, 2003 and our unpublished observations), the persistence of geminin during a checkpoint response is not sufficient to block substantial preRC reassembly. This assertion is supported by previous findings that direct inhibition of Cdk activity during G2, either pharmacologically or genetically, permits reloading of MCM proteins onto chromatin even in the presence of geminin (Bates et al, 1998;Ballabeni et al, 2004;Zhu et al, 2005). Thus, there is a risk of genome instability if preRCs are permitted to assemble while Cdk activity is inhibited.…”
Section: Discussionsupporting
confidence: 69%
“…For example, it has been shown that both CDK2 and CDK1 phosphorylate several minichromosome maintenance (MCM) factors, which are core components of a helicase complex and in their hypophosphorylated state help to unwind the DNA and establish a replication fork [36]. Loss of CDK2 function in G1 phase of the cell cycle results in reduced and suboptimal MCM4 phosphorylation in human ovarian cancer cell lines, thus, causing increased loading of the MCM complex onto chromatin and activation of checkpoint response [37]. Our proteomic analyses suggest that CDK2 interacts directly with several MCM core factors, including MCM2, MCM6, MCM7 as well as other helicases such as DHX9, SMARCA5, and replication factors including proliferating cell nuclear antigen.…”
Section: Discussionmentioning
confidence: 99%
“…CDK2 also phosphorylates minichromosome maintenance (MCM) proteins during DNA replication, thus blocking continued replication origin firing. CDK2 inhibition, therefore, causes over-replication, resulting in the formation of DSBs and single stranded DNA intermediates that activate ATM and ATR, eliciting an intra-S-phase checkpoint (38, 39). Most recently, chemical genetics experiments have revealed a non-redundant requirement for CDK2 activity in the DDR and a specific target of CDK2 (Nijmegen Breakage Syndrome gene product 1, Nbs-1) within the DNA repair machinery (40).…”
Section: New Insights Into Cdk Functions and Mechanisms Of Action mentioning
confidence: 99%